Professional training on of the protocol of reception with risk classification in pediatrics - Francisca Elisângela Teixeira Lima; Fernanda Jorge Magalhães; Alline Falconieri de Moura; Ana Paula Oliveira Queiroz; Diliane Paiva de Melo Matos; Michelle Sampaio Bezerra (Universidade Federal do Ceará, 2012)
The protocol of reception with risk evaluation and classification (RREC) in pediatrics enables the classification of children according to severity. The aim of this research was to report the experience of training a multidisciplinary team to implement the protocol RREC in pediatrics. This is an experience report of a training course of the multidisciplinary team to implement the protocol in a municipal pediatric hospital in Fortaleza, Ceará, Brazil. The project was approved by the Ethics Committee under protocol No. 80/09. The course was conducted in three stages: 1st) Opening and Presentation of the Protocol; 2nd) Activities of dispersion, and 3rd) Discussion and closure of the course. Therefore, it is believed that the use of the strategy of management training for implementation of the protocol was satisfactory, since the participants voiced an understanding of the protocol and the need to implement it because it allows for improvement in care and promotes holistic, humanized and effective care.